Importance of Serum CA 19-9 Level in Hepatolithiasis Patients Undergoing Liver Resection: serum CA 19-9 level in hepatolithiasis (Journal of Surgical Sciences, 2022)
Background: Hepatolithiasis is a known risk factor for intrahepatic cholangiocarcinoma (ICC). There is no non-invasive tool for understanding the malignant changes in biliary epithelium prior to surgery.Patients and Method: Thirty-six patients (male; 12, female; 24) with hepatolithiasis who underwent liver resection from July 2018 to June 2019 were included in the study. Operations were done left hepatectomy (58.3%), right hepatectomy 2(5.6%) and left hepatectomy with extrahepatic duct excision, clearance of right hepatic duct system followed by Roux-en-Y hepaticojejunostomy (36.1%). Serum CA 19-9 level was measured in each patient before and 7 days after surgery. Resected specimens were examined and labeled as hyperplasia, biliary intraepithelial neoplasia (BillN) and ICC. Association between preoperative serum CA 19-9 levels and biliary epithelial changes were analyzed. Postoperative serum CA 19-9 levels were compared with preoperative levels to understand the accuracy of biliary tissue removal by surgery.Results: The patients who had preoperative serum CA19-9 levels less than 100 U/ml; none had ICC. In contrast the patients who had preoperative serum CA19-9 levels more than 100U/ml; 4 (57.1%) had ICC. Further analysis showed that 80% (4/5) patients had ICC whose preoperative serum CA19-9 level was more than 1000 U/ml. The serum CA19-9 levels after liver resection were significantly reduced compared to preoperative levels in patients with BillN and CCA supports the effective removal of abnormal biliary tract.Conclusions: Preoperative serum CA19-9 level may predict ICC association with hepatolithiasis and postoperative CA19-9 level may help in accuracy of biliary tissue removal by surgery.Journal of Surgical Sciences (2022) Vol. 26(1) : 10-14